Different growing strategies of two winter wheat cultivars under rainfed conditions during dry years in North China Plain - Dong, Baodi; Yang, Hong; Qiao, Yunzhou; Zhang, Mingming; Wang, Yakai; Jin, Lele; Liu, Mengyu (International Journal of Agricultural and Biological Engineering, 2018)
The North China Plain (NCP) is a severe water shortage region, especially during the wheat growing season. Understanding the response of grain yield and water availability in winter wheat cultivars (Triticum aestivum L.) is important to adjust planting structure under groundwater reducible exploitation in rainfed dry years of NCP. Field experiments were conducted at the Luancheng Agroecosystem Experiment Station of the Chinese Academy of Sciences, Hebei, China. Two different drought resistant winter wheat cultivars (Jinmai47 and Shiluan02-1) were grown under rainfed conditions during four years of 2010-2011, 2011-2012, 2012-2013 and 2013-2014. Grain yield and its components, aboveground biomass (AB), dry matter accumulation translocation efficiency, water consumption, water use efficiency at field scale, and photosynthetic characteristics were measured. The results showed that Jinmai47 rapidly accumulated AB by higher tiller and photosynthetic potential comparing with those of Shiluan02-1. Its grain yield was 16.49% higher than that of the drought-sensitive winter wheat variety Shiluan02-1 during the four rainfed years. However, the dry matter remobilization efficiency (DMRE) and contribution of dry matter remobilization from heading stage to maturity stage to grain (CDMRE) of Shiluan02-1 was higher than those of Jinmai47. The average water use efficiency at grain yield level (WUEy), WUE at aboveground biomass level (WUEab), and WUE at grain yield under rainy conditions (WUEr) of Jinmai47 were 11.08%, 16.41%, and 17.21% higher than those of Shiluan02-1. There was a significant difference in the WUEab and WUEr between the two wheat cultivars. The two wheat varieties under drought condition have different growing strategies. Jinmai47 has more tiller number, earlier vigor, and higher AB than Shiluan02-1, helping it to adapt to the fluctuations in the environment.Keywords: winter wheat cultivar, grain yield, rainy treatment, water use efficiency, dry yearDOI: 10.25165/j.ijabe.20181105.4344Citation: Dong B D, Yang H, Qiao Y Z, Zhang M M, Wang Y K, Jin L L, et al. Different growing strategies of two winter wheat cultivars under rainfed conditions during dry years in North China Plain. Int J Agric & Biol Eng, 2018; 11(5): 150–159.